PRODUK KESEHATAN DAN PEMBENTUKAN TUBUH PEREMPUAN MUDA DI KOTA MANADO - Kalangit, Amanda L. A. (Universitas Sam Ratulangi, 2016)
Young women everyday lives in urban area is inseparable from the use of health products. Although consuming uncertain amount of these products to manage their health, sexuality, and also build their bodies, in the other hand, the number of fitness centers are also increasingly swamped by young women. It becomes a benchmark that demand for healthy lifestyles in the urban area of Manado, especially the lives of young women are growing and revived the trend of â€œidealâ€ body shape in this era. The â€œidealâ€ body is realized by means of healthy living, namely a self-management on balancing and controlling the pattern of eating right, workout, resting in proper amount of time, and etc. To achieve the â€œidealâ€ body shape as a symbol of healthy lifestyle, young women perform ways of health practices, by doing workouts such as cardio, weight lifting, Zumba, cardio, body combat and the use of health products, such as the consumption of vitamins and supplements to give nutrition from inside and outside of womenâ€™s bodies. Women and their body shape are dynamic and is a form of globalization that is found in one place very local. For young women, â€œidealâ€ body shape becomes a symbol of self-control that cannot be separated from social relations and cultural life in the urban life of Manado. Based on interviews with 18 young women in Manado, I found that young women choose these particular health practices to stay young, feel beautiful and attractive, increasing stamina, gain nutrition, feel good, neat, and confident. Hope and aspirations to live a healthy lifestyle depending on their income, demand, and social status. Keyword: youth, identity, body image, social relation, health